Rethinking Asian poverty in a time of Asian prosperity. (15th July 2018) - Rigg, Jonathan
Abstract : Southeast Asia is a development success story. By 2025, it is forecast that extreme poverty in the region will have been 'eradicated'. Does this mean that the challenges so evident in the 1960s when the countries of the region began to pursue development have been met, and the objectives achieved? The paper makes a case for thinking afresh about development and the poverty project, recognising that development is never neatly achieved but, rather, re‐worked, re‐engineered and re‐imagined over time. This is done through identifying different categories of 'poor', each produced through different poverty‐making processes, measured and viewed in different ways, and their poverty addressed using different approaches and policies. With specific reference to the cases of Laos and Thailand, and drawing on longitudinal research in the latter country, it is argued that while economic growth does trickle down, it trickles down in quite discrete and often contingent ways. Furthermore, there is always development work to be done, because development creates its own work.